W gąszczu dziecięcych potrzeb – znaczenie edukacyjne tekstów kultury popularnej na podstawie czasopisma dla dzieci pod tytułem „Świerszczyk” - Piecuch, Ewelina (Kultura-Społeczeństwo-Edukacja, 2020)
Piecuch Ewelina, In the thicket of children’s needs – educational significance of popular culture texts based on the Świerszczyk children’s magazine. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 115–132. Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.8. Children raised in today’s globalised world face an enormous, globally available and diverse range of verbal and non-verbal messages from the outside every day. In the era of prevailing consumerism, this multitude of information creates new, artificial needs that bring chaos to the children’s world. Human needs, as presented by Maslow, starting with physiological needs, through the need of safety, belonging, love, respect, knowledge and recognition are being redefined and disorganised in common understanding. The following considerations outline the result of the analysis of the content and form of several popular culture texts selected from among all the texts available on the Polish market – the Świerszczyk magazine, aimed at children.